The Effect of Using Media Video Learning to Write News on The Ability to Write News Texts in Class VIII of SMP Negeri VIII Tapung Hulu, Kampar Regency - Pinayungan Dalimunte; Yetty Morelent; Syofiani Syofiani (Jurnal Ilmiah Pendidikan Scholastic, 2023)
This study aims to determine: (1) thefeasibility of information literacy-based news writing video media for students of grade VIII SMP Negeri 1 Tapung Hulu Kampar Regency, and (2) comparison ofstudent learning outcomes taught using information literacy-based news writing video media with student learning outcomes taught without information literacy-based news writing video media. The theory that becomes the reference in this research is about video media according to Arsyad, writing news according to Zainurrahman and Djuraid. The method in this research is a quasi-experimental research with anonequivalent control groupdesign.The population of this study were all junior high school students in grade VIII of SMP N 1 Tapung Hulu. The sample of this study amounted to 2 classes with each class totaling 36 students. Class VIII-1 was taught using information literacy-based news writing video media, while class VIII-3 was taught without information literacy-based news writing video media. The object of this research is news writing video media based on information literacy.The results of this study found that: (1) Thethe results of research on the quality of video media writing news based on information literacy both by material experts, media experts, Indonesian language teachers, and students provide an assessment with a very good category, and(2)Student Learning Outcomes taught using video media writing news based on information literacy (80.00 ± 3.87) ( ±SD) were higher than the learning outcomes of students taught without video media writing news based on information literacy (68.47 ± 5.92) (t-count = 9.772; P = 0.000). Thus, learning media is a means that can be used to channel messages, stimulate thoughts, feelings, attention, and willingness of students so as to encourage the learning process in students. So that the Indonesian language learning process using video media writing news based on information literacy can improve the efficiency and effectiveness of the process and student learning outcomes for the better.